Effect of Microstructure on the Localized Corrosion and Stress Corrosion Behaviours of Plasma-Electrolytic-Oxidation-Treated AA7075 Aluminum Alloy Forging in 3.5 wt. % NaCl Solution. (26th March 2012) - Venugopal, A.; Panda, Rajiv; Manwatkar, Sushant; Sreekumar, K.; Ramakrishna, L.; Sundararajan, G.
Abstract : The influence of metallurgical heterogeneities such as coring and intermetallic phases on the corrosion and stress corrosion cracking behaviours of AA7075 aluminium alloy forging was examined in 3.5 wt. % NaCl solution with and without plasma electrolytic oxidation coating. Electrochemical test results demonstrated significant improvement in the corrosion resistance of the alloy after PEO coating. Stress corrosion results show that the metallurgical heterogeneities resulted in a loss in elongation of the uncoated sample in NaCl (11.5%) when compared to the one tested in air (12.9%). The loss in elongation of the uncoated sample was shown to be due to localized corrosion-assisted mechanical cracking rather than true stress corrosion based on preexposure tensile tests followed by posttest metallographic observation of the stress corrosion tested samples. This was further confirmed by the fractographic examination of the failed samples, which exhibited a typical ductile cracking morphology for all the coated and uncoated specimens.